HYPODERMOCLYSIS FOR UNCONVENTIONAL PEDIATRIC TREATMENTS: AN INTEGRATIVE REVIEW - Gabrielle Freitas Saganski; Márcia Helena de Souza Freire; Aneís Louise Peres; Amanda Khetleen Gusso; Suellen da Rocha Lage Moraes; Michelle Thais Migoto (Universidade Federal do Paraná, 2019)
Objective: to describe the use of hypodermoclysis in unconventional pediatric treatments. Method: an integrative review, with sampling period from 2010 to 2018, in five databases. Two independent reviewers selected the articles. Next, an evaluation of the level of evidence was performed, according to the Joanna Briggs Institute. Results: Six international articles were selected, with levels of evidence 1 and 3. The unconventional diseases and situations for treatment via hypodermoclysis were: polyarticular juvenile idiopathic arthritis; prevention of hyponatremia during fluid restriction; sedation in dental treatment; rheumatic disorders; antibiotic therapy and refractory pulmonary arterial hypertension. Conclusion: the procedure is an effective and safe option for the administration of medications in children, justified due to the minimization of pain intensity and the protection of the child, family and nursing staff from stress. However, more research is needed to substantiate it scientifically, and for its implementation in the professional practice.